Characterization of introduced breed of sheep and pattenl of conservation of Sumatera thin tail (STT) sheep in North Sumatera - Priyanto D; A.R Siregar; E Handiwirawan; Subandriyo . (Jurnal Ilmu Ternak dan Veteriner, 2000)
Sumatera thin tail (STT) sheep are highly adapted to the local environment, no seasonal reproductive activity, and highresistance to internal parasite, but they have small body size and low mature body weight. "On Fann research" to identify morphological characteristics of intoduced breed and STT sheep, as well as an altemative conservation pattem were conducted in two location, i.e. Pulahan village, Air Batu District, Asahan Regency as the potensial area for STT sheep and Pulo Gambar village, Galang District, Deli Serdang Regency as the development area of introduced breed of sheep. The approach of Agroecosystem analysis, quantitative and qualitative characteristics of STT and introduced breed of sheep as well as interview to the farmer that raised STT in order to get recommendation of conservation pattern were aplied. The study show that STT sheep were isolated from the other area, and the populations tend to decrease from year to year. Qualitative characteristics of STT indicated smaller linear body measurements than those of introducted breed of sheep at the same age. Qualitative characteristics indicated that STT possess dominance body color of light brown and white (50.93% vs 41.28%). The STT mostly have one body color pattern (61.75%). The dominance spotted pattem were 1-10% of the body (60.29%), while the dominance of the head color was light brown (48.40%). Conservation pattern of STT are through natural process, in which the farmers are directly conserved, therefore the farmers do not have opportunity to develop their sheep farming. Therefore the conservation pattern recomnendation for STT sheep are by defending the location as "in situ conservation" or "on farm conservation" and giving "compensation program" to fanner because STT sheep farming less benefit than those of introduced breed of sheep.   Key Word: Sumatera thin tail sheep, introduced breed of sheep, characterization, Conservation patter